Construction and application of a model on the resolution of tropic acid enantiomers by enantioselective liquid-liquid extraction in centrifugal contactor separators. (August 2017) - Xu, Weifeng; Wang, Shichuan; Dai, Guilin; Tang, Kewen; Zhang, Panliang; Xiong, Biquan; Liu, Yu
Graphical abstract: Highlights: Liquid-liquid extraction of TA enantiomers in centrifugal contactor separators is proposed. Thermodynamics data about the physical partition coefficients and chemical equilibrium constants are obtained. A multistage equilibrium model about the separation system is established. Model predictions can predict the experimental process very well. Purity and yield are significantly improved by changing the process parameters. Abstract: This paper reports on the construction and application of a mathematical model on multistage liquid-liquid extraction of tropic acid (TA) enantiomers in centrifugal contactor separators (CCSs). An efficient extraction system was obtained, where HE-β-CD and butyl acetate was selected as the best extractant and organic solvent. The mechanism of reactive extraction of TA enantiomers by HE-β-CD was proposed and the thermodynamic constants such as physical partition coefficient and reactive equilibrium constants were obtained, which combined with the law of mass conservation gave the basis for construction of the model. The model was applied to predict and optimize the symmetrical separation of TA enantiomers. The optimal condition was obtained as follows, O/W volume ratio of 3.0, pH of 3.00 and HE-β-CD concentration of 0.05 mol/L, where eeeq (equal enantiomeric excess) can reach up to 42%. The simulated results reveal that the minimum number of stages for eeeq  > 97% and eeeq  > 99% was 56 and 78, respectively.